General Anaesthesia for Laparoscopic Cholecystectomy in a Patient with the Kearns-Sayre Syndrome - Calzavacca, Paolo (Hindawi Publishing Corporation, 2011)
We report a case of a 40-year-old man affected by the Kearns-Sayre syndrome who underwent an elective laparoscopic cholecystectomy under general anaesthesia. We describe the management of general anaesthesia in this rare myopathy, with emphasis on the use of rocuronium as muscle blocking agent. Induction was achieved with propofol and fentanyl, and general anaesthesia was maintained with fentanyl and sevoflurane/N(2)O/O(2) mixture. The anaesthetic plan proved to be safe and effective, and extubation was achieved in the operating theatre. The postoperative recovery of the patient was satisfactory and uneventful.